2021
DOI: 10.1093/femsre/fuab004
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal tyrosine recombinases

Abstract: The integration of mobile genetic elements into their host chromosome influences the immediate fate of cellular organisms and gradually shapes their evolution. Site-specific recombinases catalyzing this integration have been extensively characterized both in bacteria and eukarya. More recently, a number of reports provided the in-depth characterization of archaeal tyrosine recombinases and highlighted new particular features not observed in the other two domains. In addition to being active in extreme environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 180 publications
0
10
0
Order By: Relevance
“…5A; Table 2). Tandem integrations have been previously described for euryarchaeal and thaumarchaeal iMGEs, including viruses, plasmids and casposons (Krupovic and Bamford, 2008; Krupovic et al ., 2019), and it has been suggested that recombination between such tandemly integrated elements promotes their modular genome evolution (Badel et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A; Table 2). Tandem integrations have been previously described for euryarchaeal and thaumarchaeal iMGEs, including viruses, plasmids and casposons (Krupovic and Bamford, 2008; Krupovic et al ., 2019), and it has been suggested that recombination between such tandemly integrated elements promotes their modular genome evolution (Badel et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…shibatae iMGEs encode both types of integrases, but all have integrated into the genome by recombining with the 3′‐distal regions of diverse tRNA genes (Table 2). Although protein‐coding genes and intergenic regions are also known to serve as integration sites for archaeal viruses and plasmids (Krupovic et al ., 2010a; Krupovic et al ., 2010b; Kazlauskas et al ., 2018; Krupovic et al ., 2019), the tRNA genes are by far the most common att sites (Badel et al ., 2021). Notably, we found that the SSV1 genome occupied not only the previously reported tRNA‐Arg (CCG) gene (Reiter et al ., 1989; Schleper et al ., 1992) but was also integrated into a secondary target site, tRNA‐Arg (TCG).…”
Section: Resultsmentioning
confidence: 99%
“…This protein family is known to be important for the integration and excision of mobile genetic elements into the host chromosome and the post-replicative segregation of plasmids and circular chromosomes in bacteria, eukaryotes and archaea [ 33 ]. Recently, new particular features were highlighted for archaeal tyrosine recombinases as catalysing reactions beyond site-specific recombination such as low-sequence specificity recombination reactions with the same outcome as homologous recombination events [ 34 ]. These low-sequence specificity recombinations might be the reason why selected mutants sometimes lose their plasmid but stay puromycin resistant by introducing the pac gene into their chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…These GIs were always missing in previously genomes assembled by short reads due to the defective resolving of repetitive fragments flanking the exogenous genetic island 33,34 . In the largest GIs of 36 Kbp, we identified six copies of Tyrosine recombinase ( xerA, xerC , or xerD ), which had previously been reported to facilitate the insertion of gene islands into the host chromosome by catalyzing site-specific, energy-independent DNA recombination 34,36 . Additionally, we identified a heat shock protein, HtpX , that may contribute to the heat shock response facilitating the cell’s survival in a thermophilic environment.…”
Section: Discussionmentioning
confidence: 99%